Pengaruh E-Servicescape dan Gamifikasi Terhadap Loyalitas Pelanggan Tokopedia (Studi Pada Pelanggan Tokopedia di Kota Surabaya) - Rias Wiranda Putri Kusnul Aprilia; Sugeng Purwanto (Journal of Economic, Bussines and Accounting (COSTING), 2023)
E-commerce companies are increasingly competitive along with the growing use of e-commerce in Indonesia. As a result, maintaining customer loyalty is an important task for companies. The purpose of this research is to find out how the e-servicescape and gamification influence the loyalty of Tokopedia customers in the city of Surabaya. The research method used is quantitative, with a sample of 100 respondents based on sample criteria. Sampling using purposive sampling approach and non-probability sampling technique. The population in this study are customers on the Tokopedia application in the city of Surabaya. Approach to data analysis using SMART PLS software. The results showed that both e-servicescape and gamification had a positive effect on consumer loyalty. Other findings showed that Tokopedia had layout and functionality as the best e-servicescape aspect while entertainment was the best gamification aspect. Keywords: E-Servicescape; Gamification; Customer Loyalty; E-Commerce